Public Child Care and Mothers' Career Trajectories - Katrin Huber; Geske Rolvering (Institute of Labor Economics (IZA), 2023)
We study the impact of public child care on mothers' career trajectories, focusing on qualitative dimensions of career choices. Using an event study approach, we find that child care helps mothers to return to the labor market more quickly and that this effect is mainly due to an increase in part-time employment. At the same time, we find no short- or long-term effects of child care on the quality of maternal careers, as measured, for example, by employment stability, employment in occupations with abstract tasks, or employment in managerial positions. Furthermore, we find no evidence of heterogeneous effects across mothers.
Keywords: J08; J13; J22; 330; child care; maternal employment; career costs of children; women's careers